Virtual impedance shaping for the bus conversion system in the hybrid AC/DC grid - Jin, Sicong (2024)
The bus conversion system in the hybrid AC/DC grid is usually composed of a three-phase interlinking converter and a DC-side input filter. The impedance interaction between the converter and the input filter may cause instability of the DC-link voltage. The previously proposed stabilization methods either require additional hardware or significantly impact the dynamic performance. Therefore, this paper presents a parallel virtual impedance regulator (PVIR), which adds desired virtual impedance in parallel with the input impedance of the converter. The proposed PVIR can precisely modify the impedance within the specific frequency range to minimize the impact on the system dynamics. The concept and detailed design procedure with the redundant design of the PVIR are introduced. The effect of the PVIR injection position is discussed. Finally, the experiment validates the effectiveness of the proposed PVIR.